2000
DOI: 10.1111/j.1749-7345.2000.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Trematode Bolbophorus confusus in Channel Catfish Ictalurus punctatus Ponds Using Salinity Manipulation and Polyculture with Black Carp Mylopharyngodon piceus

Abstract: This study evaluated the use of black carp Mylopharyngodon piceus and salinity manipulation for controlling the infection of channel catfish Ictalurus puncratus by a digenetic trematode (tentatively identified as Bolbophorus confusus). Control methods focussed mainly on the eradication of the intermediate snail host, the marsh rams‐horn Phanorbella trivolvis (previously referred to as Helisoma trivolvis), and were evaluated in laboratory tests and field experiments at a commercial catfish culture facility in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 4 publications
(2 reference statements)
3
52
0
Order By: Relevance
“…Large-scale destruction of snail populations by use of heavy machines along the shores of Annecy Lake (France) and Cultus Lake (Canada) led to substantial reductions of cercarial dermatitis (2). As for the biological control of snail populations, use of molluscivorous fish or prawns as natural snail predators is promising for long-term control (325)(326)(327)(328), although it represents a risk for native flora and fauna if nonindigenous organisms are introduced.…”
Section: Control Measures Related To the Ecology Of Avian Schistosomesmentioning
confidence: 99%
“…Large-scale destruction of snail populations by use of heavy machines along the shores of Annecy Lake (France) and Cultus Lake (Canada) led to substantial reductions of cercarial dermatitis (2). As for the biological control of snail populations, use of molluscivorous fish or prawns as natural snail predators is promising for long-term control (325)(326)(327)(328), although it represents a risk for native flora and fauna if nonindigenous organisms are introduced.…”
Section: Control Measures Related To the Ecology Of Avian Schistosomesmentioning
confidence: 99%
“…confusus. In 1999-2000, Terhune et al (2002 sampled 32 farms in Mississippi and reported at least 32% of 821 ponds positive for B. confusus. Many farmers thought that ridding ponds of the reported host for B. confusus, the American white pelican, would solve the problem.…”
mentioning
confidence: 99%
“…Many natural enemies of snails may have the potential to reduce snail density, but emphasis has been on competitor snails or predators (Madsen 1983). Biological control of snails may be achieved by the introduction of competitor snails, and there have been examples of the natural displacement of snails transmitting schistosomes in the field ( Nguyen Manh Hung et al 252 With varying success, species of mollusk-eating fishes have been tested as snail control agents (Shelton et al 1995;Venable et al 2000;Rothbard and Rubinshtein 2000;Ben-Ami and Heller 2001;Terhune et al 2003;El-Deeb and Ismail 2004;Ledford and Kelly 2007;Wui and Engle 2007), e.g. the Haplochromine cichlid Astatoreochromis alluaudi, Reader Sunfish Lepomis microlophus, Blue Catfish Ictalurus furcatus etc., especially, Black Carp, Mylopharyngodon piceus, stands out as an efficient predator of snails.…”
Section: Snail Controlmentioning
confidence: 99%